PERSIS Perspective: Hadits Stance on The Dead’s Torture Due to Family’s Lamentation - Rafid Abbas (Islamika Inside: Jurnal Keislaman dan Humaniora, 2023)
Abstract: PERSIS is a religious organization which actively involved in the field of hadith. Its activities started with routine learning groups of hadiths and Qur’an discussions, especially in relation to Islamic laws which then developed into a movement for organizational reforms. PERSIS argues that all hadiths must get through an initial assessment for their authenticity, both for the history of narrations and its authentic contents as narration validity becomes a regular problem due to its contradiction with the more valid texts. The study deploys a descriptive analytic method to analyze data and make classification before the conclusion is taken concerning the book writing. For instance, the hadith as narrated by Umar bin Khattab states that a dead body will be tortured because of the family members mourning. However, Aisha denied the authenticity of Umar’s narration by proposing the Qur'an argument. Apparently, Umar relied on what he overheard from the Messenger with no Quranic support. Whereas, Aisyah referred to the history of a specific verse in the Qur’an even though what came from the Prophet was normally the interpretation of Quranic verses. In this study, PERSIS compiled different opinions among the messenger’s friends and family’s opinions about whether or not dead muslims were tortured in the grave due to the families’ mourning and lamentation.